2020
DOI: 10.3390/su12062232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leverage on Real Earnings Management: Evidence from Korea

Abstract: This study examines how leverage affects real earnings management (REM) in non-financial firms listed on the Korea Composite Stock Price Index from 2010 to 2018 by employing total, short-term, and long-term debt ratios (i.e., leverage) as independent variables and four REM metrics as dependent variables. We find a significant positive relationship between leverage and REM in suspicious firms, whereas the effect of leverage is insignificant in non-suspicious firms. We also find that the positive relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
6
0
3
Order By: Relevance
“…Dalam penelitian ini ada enam variabel kontrol yaitu asset tangibility, umur perusahaan, net interest payment, pertumbuhan penjualan, return on assets dan kas. Asset tangibility diukur dengan membagikan aset tetap pada jumlah aset (Tulcanaza-Prieto et al, 2020). Umur perusahaan diukur dengan jumlah tahun perusahaan tersebut telah berjalan (Alhmood et al, 2020;Qawasmeh & Azzam, 2020).…”
Section: π‘…π‘Žπ‘ π‘–π‘œ π‘ˆπ‘‘π‘Žπ‘›π‘” π½π‘Žπ‘›π‘”π‘˜π‘Ž π‘ƒπ‘’π‘›π‘‘π‘’π‘˜ = π‘ˆπ‘‘π‘Žπ‘›π‘” π½π‘Žπ‘›π‘”π‘˜π‘Ž π‘ƒπ‘’π‘›π‘‘π‘’π‘˜ π½π‘’π‘šπ‘™π‘Žβ„Ž πΏπ‘–π‘Žπ‘π‘–π‘™π‘–π‘‘π‘–π‘Žπ‘ unclassified
See 2 more Smart Citations
“…Dalam penelitian ini ada enam variabel kontrol yaitu asset tangibility, umur perusahaan, net interest payment, pertumbuhan penjualan, return on assets dan kas. Asset tangibility diukur dengan membagikan aset tetap pada jumlah aset (Tulcanaza-Prieto et al, 2020). Umur perusahaan diukur dengan jumlah tahun perusahaan tersebut telah berjalan (Alhmood et al, 2020;Qawasmeh & Azzam, 2020).…”
Section: π‘…π‘Žπ‘ π‘–π‘œ π‘ˆπ‘‘π‘Žπ‘›π‘” π½π‘Žπ‘›π‘”π‘˜π‘Ž π‘ƒπ‘’π‘›π‘‘π‘’π‘˜ = π‘ˆπ‘‘π‘Žπ‘›π‘” π½π‘Žπ‘›π‘”π‘˜π‘Ž π‘ƒπ‘’π‘›π‘‘π‘’π‘˜ π½π‘’π‘šπ‘™π‘Žβ„Ž πΏπ‘–π‘Žπ‘π‘–π‘™π‘–π‘‘π‘–π‘Žπ‘ unclassified
“…Ukuran perusahaan memiliki pengaruh signifikan negatif terhadap manajemen laba sehingga semakin besar perusahaan dengan transaksi dan operasional yang banyak justru memicu manajemen untuk melakukan manipulasi laba seperti dengan mengurangi biaya pajak. Maka, hipotesis 4 diterima dan selaras dengan penelitian Mahawyahrti & Budiasih (2017) dan Tulcanaza-Prieto et al (2020). Rasio lancar memiliki hasil yang tidak signifikan, sehingga kemampuan perusahaan dalam membayar utang lancarnya tidak mempengaruhi keputusan manajemen untuk mencoba melakukan manipulasi laba.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…The study concluded that when companies experience financial difficulties, they will carry out earnings management by changing their operating profits. Nevertheless, there is also the proof that companies undertake real earnings management (Kothari et al, 2016;Nasir et al, 2018;Tulcanaza-Prieto et al, 2020) and real earnings management might have a bigger effect than accrual earnings management since it is not only revamping the accounting records but also the behavior of the firm. Besides, accrual-based earnings management is vulnerable to scrutiny, therefore, can be easily noticed by auditors and regulators.…”
Section: Financial Distress and Earnings Managementmentioning
confidence: 99%
“…Roychowdhury (Roychowdhury, 2006) documents that managers from high-leverage firms manipulate real earnings, activities by, (1) providing price discounts to temporarily increase the sales volume, (2) overproducing inventory to decrease the cost of goods sold (COGS), or (3) cutting discretionary expenses to improve the reported margins. Tulcanaza-Prieto, Lee, and Koo (Tulcanaza-Prieto, Lee, et al, 2020) also reports the positive relationship between leverage and REM using quarterly financial data. Therefore, firms might increase their REM activities (1) to show stable results and fewer volatile earnings to their lenders and future investors (Burgstahler & Dichev, 1997;Wijesinghe & Kavinda, 2017), (2) to reduce their debt covenant violations, contraventions, and penalties (Y.…”
Section: β…° Introductionmentioning
confidence: 99%